650 GHz SIS mixer fabricated on silicon‐on‐insulator substrate. Issue 20 (1st September 2013) - Tan, B.‐K.; Yassin, G.; Grimes, P.; Jacobs, K.
Abstract : The successful operation of a 650 GHz unilateral finline superconductor–insulator–superconductor mixer with a wide IF bandwidth is reported. The mixer was fabricated using silicon‐on‐insulator (SOI) technology, with planar circuit on‐chip integration. The mixer was tested over the frequency range of 630–702 GHz, and the best recorded DSB noise temperature was 226 K. The measured RF and IF behaviour of the mixer agreed very well with the simulation predictions. This demonstrates that superconducting finline mixers fabricated on an SOI substrate can achieve state‐of‐the‐art performance, and yet are much more compact and highly reproducible, and hence suitable for large‐format arrays in astronomy instruments, at THz frequencies.